AI ChatGPT Based Islamic Religious Education to Enhance Students’ Critical Thinking and Moral Reasoning - Salim, M Agus; Habibi, Fajri (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
Higher education increasingly leverages artificial intelligence (AI) to foster higher-order cognitive skills; however, in Indonesia, students of Islamic Religious Education (PAI) often depend on rote memorization, limiting the growth of critical thinking and moral reasoning. This study aimed to determine the effectiveness of a ChatGPT-based PAI learning model in enhancing students’ dual thinking abilities. A mixed-methods quasi-experimental design was implemented with 32 undergraduate students assigned equally to experimental and control groups; instruments comprised a critical thinking test, a moral reasoning test contextualized with Islamic dilemmas, and a transcript analysis guide, all expert-validated. Quantitative results showed notable post-test gains in the experimental group for critical thinking (M = 78.6, SD = 7.8) and moral reasoning (M = 76.8, SD = 7.9), while qualitative analysis indicated that 56.3% of students reached advanced critical thinking levels and 68.8% demonstrated advanced moral reasoning. The findings indicate that integrating ChatGPT enhances both cognitive and affective learning outcomes in PAI. The study concludes that a ChatGPT-based model is effective for strengthening critical thinking and moral reasoning, and contributes empirical evidence on generative AI in Islamic education; practically, it underscores ChatGPT’s utility as a dialogic partner when guided by lecturers. The implications include scaling to larger samples and longer interventions and exploring adaptive prompting strategies across diverse educational contexts.